Limited Success of Spat Ropes and Rubber Ramps for Restoring Fish Passage at a Perched Culvert - Sjaan Bowie; Nixie Boddy; Cindy F. Baker; Jonny Horrox; Paul A. Franklin (New Zealand Journal of Marine and Freshwater Research, 2026)
Many culverts in New Zealand rivers are poorly designed or maintained, impeding fish migrations. This study tested three low‐cost fish passage solutions—mussel spat ropes, a flexible rubber ramp, and a combination of both—at a perched culvert apron on the West Coast. Passage efficiency was assessed for three indicator species with different locomotive capabilities: īnanga ( Galaxias maculatus ), redfin bully ( Gobiomorphus huttoni ), and banded kōkopu ( Galaxias fasciatus ). Spat rope and rubber ramp both independently and in combination were ineffective at facilitating passage of īnanga or redfin bully. The combination of spat rope and rubber ramp moderately increased banded kōkopu passage, predominantly for fish